2019
DOI: 10.1007/s41465-019-00139-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Resveratrol Administration Increases Neural Effort but Not Whole Body Metabolism or Cognitive Performance in Healthy, Young Participants

Abstract: Research into the cognitive enhancing effects of polyphenols is small but growing. Single doses of the stilbene polyphenol resveratrol can increase cerebral blood flow (CBF) but have failed to improve cognitive performance in young, healthy cohorts. As both CBF and overall energy expenditure are closely related to neural activity, this randomised, double-blind, placebocontrolled, crossover investigation, assessed the metabolic consequences of resveratrol during high cognitive demand via indirect calorimetry (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…As quercetin, resveratrol also shows a promising effects in athletic men and women [165][166][167][168]. Particularly, Eschle and colleagues [169] reported that daily supplementation of 500 mg resveratrol can significantly increase respiratory exchange by improving carbohydrate oxidation during cognitive demands. It was also reported that its supplementation (3 g/day) for 12 weeks increased skeletal muscle SIRT1 expression and energy expenditure by upregulating AMPK expression in patients with type 2 diabetes mellitus [170].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…As quercetin, resveratrol also shows a promising effects in athletic men and women [165][166][167][168]. Particularly, Eschle and colleagues [169] reported that daily supplementation of 500 mg resveratrol can significantly increase respiratory exchange by improving carbohydrate oxidation during cognitive demands. It was also reported that its supplementation (3 g/day) for 12 weeks increased skeletal muscle SIRT1 expression and energy expenditure by upregulating AMPK expression in patients with type 2 diabetes mellitus [170].…”
Section: Clinical Studiesmentioning
confidence: 99%